Platelet / spleen ratio for the diagnosis of esophageal varices and the risk of bleeding in patients with liver failure: Cociente plaquetas/bazo para el diagnóstico de várices esofágicas y riesgo de sangrado en pacientes con insuficiencia hepática - Montiel Jarquín, Álvaro José (2021)
Introduction: Upper gastrointestinal bleeding of variceal origin has a high mortality. The platelet count/spleen major diameter ratio may be a useful noninvasive parameter to predict esophageal variceal bleeding in cirrhotic patients. Objective: to determine the sensitivity and specificity of the platelet count/spleen diameter ratio for the diagnosis of esophageal varices with risk of bleeding in patients with hepatic insufficiency. Material and Methods: Process study, performed in a Second Level Medical Facility, in patients with liver failure who underwent ultrasound, blood cytometry, liver function tests and endoscopy. Sensitivity and specificity of the platelet/spleen ratio were assessed in patients with esophageal variceal and bleeding risk. Results: There were 70 patients: 28 women, 42 men; main cause of liver failure in men was ethylism in 31 patients and hepatitis C virus in 20 women. The spleen-platelet ratio has a sensitivity of 90%, specificity 83%, false positives 16%, false negatives 9%, positive predictive value 94%, negative predictive value 75%, prevalence of 74% and diagnostic accuracy of 88% to diagnose esophageal varices with risk of bleeding. Conclusion: Platelet/spleen ratio is a useful, non-invasive study to diagnose esophageal varices with bleeding risk, in hospitals where endoscopy is not available.